Ranch Apocalypse: A Pataphysical Inquiry into the Mount Carmel Siege - Granden, Michelle (International Journal of Criminology and Sociology, 2012)
A total of 84 people were killed in the 1993 Bureau of Alcohol, Tobacco, and Firearms (ATF) raid on Mount Carmel in Waco, Texas. Debates continue about who was responsible—e.g., was it a government conspiracy or cultist militants intent on mass suicide? What hasn’t been fully considered, however, is the role the guns, tanks, toxic gases, and other “theater of war” accoutrements themselves played in the siege and resultant deadly inferno. Traditional metaphysical inquiries rest on the presupposition that the subject is separate from and sovereign over the object it examines. But as we have entered this intensely visual consumer culture, differences between subject and object disappear and the power of the subject collapses. Employing the postmodern metaphysics—here and elsewhere called “pataphysics”—of Jean Baudrillard to investigate this tragic battle, the author will argue that the ATF and the FBI were seduced by the compound’s castle and arsenal as well as their own. The helicopters, snipers, tanks, and CS gas turned what had begun on February 28, 1993, as a raid to serve a search warrant into a full scale military-style attack on a fortress and its peoples. Could it be that the federal agents became and were subordinate to the tools they were using?